A review on energy chemistry of fast-charging anodes. (1st June 2020) - Cai, Wenlong; Yao, Yu-Xing; Zhu, Gao-Long; Yan, Chong; Jiang, Li-Li; He, Chuanxin; Huang, Jia-Qi; Zhang, Qiang
Abstract : Fundamentals, challenges, and solutions towards fast-charging graphite anodes are summarized in this review, with insights into the future research and development to enable batteries suitable for fast-charging application. Abstract : With the impetus to accelerate worldwide market adoption of electrical vehicles and afford consumer electronics with better user experience, advancing fast-charging technology is an inevitable trend. However, current high-energy lithium-ion batteries are unable to support ultrafast power input without any adverse consequences, with the capacity fade and safety concerns of the mainstream graphite-based anodes being the key technological barrier. The aim of this review is to summarise the fundamentals, challenges, and solutions to enable graphite anodes that are capable of high-rate charging. First, we explore the complicated yet intriguing graphite–electrolyte interface during intercalation based on existing theories. Second, we analyse the key dilemmas facing fast-charging graphite anodes. Finally, some promising strategies proposed during the past few years are highlighted so as to outline current trends and future perspectives in this field.